2021
DOI: 10.3389/fnbeh.2021.632143
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 4-Phenylbutyrate Protects Hypoxic-Ischemic Brain Injury via Attenuating Endoplasmic Reticulum Stress in Neonatal Rats

Abstract: Neonatal hypoxic-ischemic (HI) brain injury is associated with long-term neurological disorders, and protective strategies are presently scarce. Sodium 4-phenylbutyrate (4-PBA) reportedly acts as a chemical chaperone that alleviates endoplasmic reticulum (ER) stress, which plays a critical role in neurological diseases. The present study aimed to evaluate the neuroprotective effects of 4-PBA on HI-induced neonatal brain injury in a rat model, and to characterize possible underlying mechanisms. The HI brain inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In this study, ERS-related genes ( ATF6 , XBP-1 , GRP78 , CHOPα , and Eif2α ) and key proteins (XBP-1, GRP78, and Eif2α) were markedly upregulated in the HC group, but intestinal ERS was significantly alleviated in juvenile largemouth bass following the addition of SA and SB to the diet. Previous studies have demonstrated that SA and SB can ameliorate tissue damage by attenuating ERS in the brain, liver, and intestine of mice ( Hu et al., 2018 ; Wu et al., 2021 ; Zhang et al., 2016 ). However, few studies have examined the effect of adding SA and SB to the diet on ameliorating HC-induced intestinal ERS in fish.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ERS-related genes ( ATF6 , XBP-1 , GRP78 , CHOPα , and Eif2α ) and key proteins (XBP-1, GRP78, and Eif2α) were markedly upregulated in the HC group, but intestinal ERS was significantly alleviated in juvenile largemouth bass following the addition of SA and SB to the diet. Previous studies have demonstrated that SA and SB can ameliorate tissue damage by attenuating ERS in the brain, liver, and intestine of mice ( Hu et al., 2018 ; Wu et al., 2021 ; Zhang et al., 2016 ). However, few studies have examined the effect of adding SA and SB to the diet on ameliorating HC-induced intestinal ERS in fish.…”
Section: Discussionmentioning
confidence: 99%